IMPLEMENTASI PEMBIASAAN SHOLAT BERJAMAAH DALAM MEMBENTUK KARAKTER SISWA DI SMA MA’ARIF SUKOREJO - Muhammad Rizal Fatkhur Rohman; Yusuf, Achmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education is an essential aspect of the educational process, aiming not only to develop students’ academic abilities but also to foster positive attitudes and behaviors. One of the strategies implemented by schools to strengthen character education is the habituation of congregational prayer activities. This study aimed to analyze the implementation of congregational prayer habituation in shaping students’ character at SMA Ma’arif Sukorejo, identify the characters developed through the activity, and examine the supporting and inhibiting factors in its implementation. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving the principal, Islamic education teachers, and students. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the habituation of congregational prayer played a significant role in developing students’ character, particularly discipline, responsibility, religiosity, obedience, and social awareness. The success of the program was supported by the school’s commitment, teachers’ exemplary behavior, and adequate worship facilities. However, several obstacles were identified, including students’ low self-awareness and limited internal motivation to participate consistently. Therefore, the habituation of congregational prayer can be considered an effective strategy for strengthening character education and fostering positive behavior among students in the school environment.